Impact of precursor preparation on density of gadolinium iron garnets synthesized via reactive sintering. Issue 17 (1st September 2021) - Lach, R.; Stan, M.; Łańcucki, Ł.; Gajewska, M.
Abstract: Gadolinium iron garnet was obtained from two different precursors, homogenized in isopropyl alcohol and in an aqueous environment with a fixed pH. In the first case, it was a mixture of goethite (FeO(OH)) and gadolinium oxide (Gd2 O3 ); in the second, a mixture of GdIP (GdFeO3 ) and α-Fe2 O3 . Conditions of homogenization in the aqueous environment were selected based on the zeta (ξ) potential measurements as the function of pH. DSC measurements of the output powder mixtures allowed the identification of the effects observed during the temperature rise. In the case of the material obtained from a mixture of goethite (FeO(OH)) and gadolinium oxide, with the increasing temperature, we observe three effects, the first of which corresponds to the phase transformation of goethite into α-Fe2 O3, the second corresponds to the reaction of gadolinium iron perovskite (GdIP) formation, and the third to the reaction in which a gadolinium iron garnet (GdIG) is formed. However, in the case of heat treatment of the mixture of GdIP and α-Fe2 O3, we only observe the effect responsible for a solid state reaction leading to the formation of gadolinium iron garnet. Dilatometric measurements allowed to determine the changes in linear dimensions at various stages of reaction sintering. The resulting materials were sintered at temperatures of 1200, 1300, and 1400 °C. In the case of the material obtained from a mixture of perovskite and iron (III) oxide, already at the temperature of 1300 °C, a density has been obtained at around 95% of the theoretical density, and the temperature of 1400 °C allowed achieving a density of 97% of the theoretical density. Whereas, for the material obtained from a mixture of goethite (FeO(OH)) and gadolinium oxide, a density above 95% of theoretical density was achieved only at 1400 °C.